The Effect of Merger and Acquisition on Employee’s Morale and Credit Performance in Nepalese Commercial Banks - Shrestha, Shubhash; Sah, Puja (Nepalese Journal of Economics, 2024)
This study examines the effect of mergers and acquisitions on employee’s morale and credit performance in Nepalese commercial banks. Employee morale (EM) and credit to deposit ratio (CDR) are the selected dependent variables. The selected independent variables are employee remuneration, job security, employee responsibility, chain of command, employee social status, and sense of belongingness. The study is based on primary and secondary data of 18 commercial banks with 122 respondents. To achieve the purpose of the study, structured questionnaire is prepared. Secondary data were collected from Banking and Financial Statistics published by Nepal Rastra Bank and annual reports of the selected commercial banks. The correlation coefficients and regression models are estimated to test the significance and importance of the effect of mergers and acquisitions on employee’s morale and credit performance in Nepalese commercial banks. The study showed that job security has a positive impact on employee morale and credit to deposit ratio. It indicates that an increase in job security leads to an increase in employee morale and credit to deposit ratio. Similarly, employee remuneration has a positive impact on employee morale. It indicates that an increase in employee remuneration leads to an increase in employee morale. In contrast, employee remuneration has a negative impact on credit to deposit ratio. It indicates that an increase in employee remuneration leads to decrease in credit to deposit ratio. Likewise, employee sense of belongingness has a positive impact on employee morale and credit to deposit ratio. It indicates that higher the employee sense of belongingness, higher would be the employee morale and credit to deposit ratio. Further, chain of command has a positive impact on employee morale and credit to deposit ratio. It indicates higher the chain of command, higher would be the employee morale and credit to deposit ratio. In addition, employee responsibility has a positive impact on employee morale and credit to deposit ratio. It indicates that an increase in employee responsibility leads to an increase in employee morale and credit to deposit ratio. Moreover, employee social status has a positive impact on employee morale and credit to deposit ratio. It indicates that higher the employee social status, higher would be the employee morale and credit to deposit ratio.